192k views
9 votes
Change from typical notation to function notation

y = 5x - 2

User Big Lep
by
5.0k points

2 Answers

2 votes

Let's see


\\ \rm\rightarrowtail y=5x-2

  • . Function notation.


\\ \rm\rightarrowtail g(x)=5x-2

Some test

  • g(2)=5(2)-2=8
User Poncha
by
4.9k points
9 votes

Answer:

f(x) = 5x - 2

Explanation:

To change from typical notation to function notation, simply replace y with f(x). Remember to ensure the variable you put in the brackets is the same as the variable in the equation.

So y = 5x - 2 becomes f(x) = 5x - 2 (since the variable is x)

And y = 5a - 2 becomes f(a) = 5a - 2 (since the variable is a)

The typical letter to use is f, but we can use other letters.

Other common function notations are g(x) and h(x).

User Nathan Pitman
by
5.3k points